2012
DOI: 10.1111/j.1600-051x.2012.01917.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and immunosuppressive properties of mesenchymal stem cells from periapical lesions

Abstract: The differentiation potential of PL-MSCs and their immunosuppressive/anti-inflammatory properties could be beneficial for the treatment of chronic periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 55 publications
6
40
0
1
Order By: Relevance
“…We have previously described in details morphological, phenotypical and differentiation characteristics of PL-MSCs isolated from three different donors (12). In this work we used one of the lines to study its immunoregulatory properties.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously described in details morphological, phenotypical and differentiation characteristics of PL-MSCs isolated from three different donors (12). In this work we used one of the lines to study its immunoregulatory properties.…”
Section: Resultsmentioning
confidence: 99%
“…We found that STRO-1, a marker for MSCs (15), showed a lower membrane expression. However, this marker including CD46, was localized predominately intracellularly, as demonstrated by immunochystochemistry (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations